Gothic Paleography and the Preface to the First Edition of The Castle of Otranto. Issue 2 (November 2019) - Yeager, Stephen
Abstract : The first-edition preface to Walpole's novel The Castle of Otranto contains a description of an imagined incunabulum, ostensibly witnessing the novel's text, which is attributed to an imagined translator, William Marshall. The incunabulum is said by Marshall to be printed in a 'black letter' typeface, a term which was already in this period a synonym for 'gothic' letterforms. This essay briefly summarizes the history of this classificatory term 'gothic' as it is applied to script, in order to provide further context for Walpole's parody of antiquarianism in the first edition preface and its relation to his use of the term 'gothic' in the subtitle to the novel's second edition.